Ionospheric response to the 3 August 2010 geomagnetic storm at mid and mid-high latitudes - Mansilla, Gustavo Adolfo (2013)
The global ionospheric response to the geomagnetic storm occurred of 3 August 2010 is studied in terms of the ionospheric parameter foF2. Data from three longitudinal sectors (Asia/Paciﬁc, Europe/Africa and America) are considered. Some new aspects of the storm time ionospheric behavior are revealed. Results of the analysis show that the main ionospheric effects of the storm under consideration are: (a) prior to the storm, Japanese, Australian and American stations show increases in foF2, irrespective of the local time. (b) During the main phase, the stations of mid latitudes of the American sector show positive disturbances (in the pre-dusk hours), which subsequently change to negative. (c) During the recovery phase of the magnetic storm long-duration positive disturbances are observed at mid-low latitudes of the African chain. Also positive disturbances are observed in the Australian sector. In the European sector long duration negative disturbances are seen at mid-high latitudes during the last part of the recovery phase while at mid- low latitudes a positive disturbance is seen, followed by a negative disturbance. In general, the ionospheric storm effects show a clear hemispheric asymmetry.